The role of elephants (Loxodonta Africana Blumenbach) in forest savanna vegetation in Rabongo forest, Uganda - Nampindo, S. (Makerere University, 2005)
The Rabongo Forest is located in western Uganda. It is a very important forest for biodiversity and supports large herbivores such as elephants, buffaloes and frugivores (e.g. monkeys, and chimpanzees). The aim of the study was to examine the role of elephant foraging in influencing regeneration, forest composition and species diversity in Rabongo forest. Data were collected by complete re-measurement of seven one ha plots established in Rabongo Forest in 1992 by Douglas Sheil. Seedlings, samplings and trees, were enumerated and diameter at reference height (DRH) measured for all trees of (DRH ³ 10 cm) from sub plots measuring 20 m x 20 m. Results showed that there was an increase in stem density where a total of 3332 stems were recorded in 2001 census compared to 2474 stems in 1992. It is concluded that elephant foraging enhanced tree species diversity and forest regeneration. Rabongo forest is not likely to change to savanna grasslands given the current elephant foraging. Based on the results, it is recommended that monitoring of elephant populations and forest ecosystem for possible threats to conservation must be strengthened by park management. Activities such as landscape management, control of illegal poaching that have the potential to lead to sustainable elephant populations and forest cover should be promoted by Uganda Wildlife Authority and conservationists.